English as a foreign language for deaf and hard-of-hearing persons challenges and strategies - Domagała-Zyśk, Ewa; Kontra, Edit H. (Cambridge Scholars Publishing, 2016)
Deaf and hard-of-hearing students form a specific group of foreign language learners. They need to use foreign languages just like their hearing peers if they want to enjoy the same benefits of globalization and technical advancements of today, yet they cannot take part in the same foreign language education